2004
DOI: 10.1111/j.1527-3458.2004.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Pharmacological and Clinical Profile of Rimcazole

Abstract: Rimcazole is a carbazole derivative that acts in part as a sigma receptor antagonist. Wellcome Research Laboratories introduced this compound during the 1980s when it was hypothesized to be a novel antipsychotic with an improved side effect profile. However, subsequent clinical trials demonstrated that rimcazole lacked efficacy in schizophrenic patients and it is now primarily used as an experimental tool. In addition to its actions as a sigma receptor antagonist, rimcazole also has high affinity for dopamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 131 publications
0
23
0
1
Order By: Relevance
“…Indeed, we were able to produce a dose-response curve in the absence of Fura-2-loaded cells with an apparent EC50 of approximately 10 mM (data not shown). However, rimcazole did not interfere with the reading of the MTS assay, and was found to inhibit metabolic activity of MDA-MB-468 cells with a pIC50 4.4 Ϯ 0.2 (n = 5; IC50 45 mM) which is over 30 times higher than the published affinity for the sigma-1 receptor (0.9 mM; Gilmore et al, 2004). The affinity of rimcazole was therefore assessed, and the effect of GTP on rimca- zole binding measured in Figure 6.…”
Section: Figurementioning
confidence: 84%
See 2 more Smart Citations
“…Indeed, we were able to produce a dose-response curve in the absence of Fura-2-loaded cells with an apparent EC50 of approximately 10 mM (data not shown). However, rimcazole did not interfere with the reading of the MTS assay, and was found to inhibit metabolic activity of MDA-MB-468 cells with a pIC50 4.4 Ϯ 0.2 (n = 5; IC50 45 mM) which is over 30 times higher than the published affinity for the sigma-1 receptor (0.9 mM; Gilmore et al, 2004). The affinity of rimcazole was therefore assessed, and the effect of GTP on rimca- zole binding measured in Figure 6.…”
Section: Figurementioning
confidence: 84%
“…We also tested a second sigma-1 receptor antagonist, rimcazole, which has a published affinity for this receptor of 0.9 mM (Gilmore et al, 2004) and has been previously shown to cause apoptosis in cancer cells through a sigma-1 receptordependent pathway (Spruce et al, 2004). We were unable to use rimcazole in the calcium assay as it interfered with the wavelengths at which Fura-2 is read, fluorescing intensely at 510 nm.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Afobazole was applied at 30 mM in the absence and presence of the selective s-1-and s-2-receptor antagonist BD-1047 (10 mM) (Matsumoto et al, 1995) and rimcazole (300 nM) (Gilmore et al, 2004), and migration in response to Ab 25-35 was assessed. Afobazole alone decreased microglial migration caused by Ab 25-35 by 29 6 1%.…”
Section: Resultsmentioning
confidence: 99%
“…Although rimcazole itself is a non-selective s ligand that also binds the dopamine transporter (Gilmore et al, 2004), highly specific small molecule s-1 agonists do exist. In s-1 knockout mice, binding of brain membranes to the s-1 agonist ( þ )-pentazocine is abolished, providing evidence that ( þ )-pentazocine acts solely through s-1 sites (Langa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%